RE-OS SYSTEMATICS OF EARLY PROTEROZOIC FERROPICRITES, PECHENGA COMPLEX, NORTHWESTERN RUSSIA: EVIDENCE FOR ANCIENT 187OS-ENRICHED PLUMES - Walker R.J.; Morgan J.W.; Hanski E.J.; Smolkin V.F. (My University, 1997)
The Re-Os isotopic systematics of various ferropicritic flows and sills of the Pechenga Complex, Russia, have been examined. During crystallization about 1.98 Ga ago, many of these bodies became highly differentiated. In addition, some of the larger igneous units are associated with major NiCu ore deposits. The melts that produced these rocks have been termed ferropicritic because of their high FeO and MgO contents. They are also enriched in light rare earth elements (LREEs), TiO2, Zr, and many other incompatible trace elements. Previous studies have concluded that the ferropicrites were most likely derived from an Fe-rich mantle plume that had a complex history of long-term LREE depletion (initial ϵNd = + 1.4), but that also experienced a LREE enrichment event within 200 Ma of the generation of the rocks.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой